2022
DOI: 10.1016/j.jcmgh.2021.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Mutation/Activation Is Dispensable for the Development of Chemically Induced Mouse HCC

Abstract: Unlike human and rat hepatocellular carcinoma, chemically induced mouse hepatocellular carcinomas do not show Nrf2 mutation/activation. Furthermore, metabolic reprogramming of neoplastic cells is absent as well. The results suggest that the mouse is not the ideal model to investigate the role of nuclear factor (erythroid-derived 2)-like 2 in hepatocarcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Mechanistic studies in animal models of liver carcinogenesis described a synergistic effect of Nrf2 and β-catenin in cancer initiation and progression. Most Recently, Mattu et al showed that a gain of function mutation of the gene for Nrf2 is not mandatory for the development of chemically induced HCC in mice but not in human and rat [ 61 ]. Nevertheless, Zavattari et al (2015) showed that Nrf2 is activated early in HCC formation and is probably essential for clonal expansion of preneoplastic hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic studies in animal models of liver carcinogenesis described a synergistic effect of Nrf2 and β-catenin in cancer initiation and progression. Most Recently, Mattu et al showed that a gain of function mutation of the gene for Nrf2 is not mandatory for the development of chemically induced HCC in mice but not in human and rat [ 61 ]. Nevertheless, Zavattari et al (2015) showed that Nrf2 is activated early in HCC formation and is probably essential for clonal expansion of preneoplastic hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the presence of cellular stress, Keap1 undergoes conformational changes, blocking NRF2 degradation and allowing its nuclear translocation, leading to the transactivation of antioxidant genes, thus inhibiting ferroptosis [ 61 , 62 ]. In HCC, NRF2 mutations accounted for approximately 15% of patients [ 63 ]. When HCC cells were exposed to ferroptosis inducers including sorafenib, buthionine sulfoximine, and erastin, there was an upregulation of p62 [ 64 , 65 ].…”
Section: The Molecular Pathways Of Ferroptosis In Hccmentioning
confidence: 99%